TRADE BUILDINGS "TIM" DURING THE TIMURIDS AND KHANATES (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article describes the history of «Tim» markets and their current functions, the restoration of trade routes in the era of Amir Temur and the Timurids, the development of the later commercial buildings and activities of the Timurids and Khans.